Effect of Educator’s Soft Skills, Organization Atmosphere, and Academic Stress on the Self-efficacy of the Army’s NCO Cadets in Rindam Jaya Jakarta - Hardi, Hardi; Ekosiswoyo, Rasdi; Sugiharto, Dwi Yuwono Puji; Prihatini, Titi (The Journal of Educational Development, 2018)
Educator’s Soft skills are parts of the personality competencies that have been established by the law to be among the competencies that must be possessed by teachers and lecturers. Basically, the success of education to achieve a goal depends on the individuals’ ability to carry out their duties. The main purpose of this study is to explain the effect of educator’s soft skills, organization atmosphere, and academic stress on the self-efficacy of the Army’s NCO Cadets in Rindam Jaya Jakarta. The population of this study was 188 NCO Cadets in the institution. 113 samples were selected using a random sampling technique. The results of the study show that (1) the educator’s soft skills provide a significant effect on academic stress; (2) the educational organization atmosphere provides a significant effect on academic stress, (3) the educator’s soft skills and organization atmosphere provide a significant effect on academic stress; (4) the academic stress provides significant effect on self efficacy; (5) the educator’s soft skills, educational organization atmosphere, and academic stress significantly influence the self-efficacy of the Army’s NCO Cadets. The conclusion is that the self-efficacy of the cadets is highly dependent on the educator’s soft skills, organization atmosphere, and academic stress.